A Comparative Study to Identify Risk Factors Associated with Non-Communicable Diseases Among Migrants and Non-Migrants in an Urban Slum Using the WHO STEPS Approach - Srivastava, Neelam; B. Telang, Bharatbhushan (Journal of Neonatal Surgery, 2025)
Background:Noncommunicable diseases (NCDs) pose a rising burden globally, with a disproportionate impact on urban slum dwellers and vulnerable populations like migrants due to unhealthy lifestyle and limited healthcare access. Objectives:To compare the prevalence of risk factors for NCDs among migrants and non-migrants living in an urban slum, using the World Health Organization (WHO) STEPwise approach to NCD risk factor surveillance (STEPS). Methods:A cross-sectional observational study was conducted among 286 participants (143 migrants and 143 non-migrants with the mean age of 40.2 years) in an urban slum in a metropolitan city of Maharashtra. Stratified random sampling was employed. Data were collected using a pre-tested questionnaire based on the WHO STEPS. Additionally anthropometric, biochemical, and clinical parameters were recorded. Results:Migrants exhibited significantly higher prevalence of hypertension (53.1% vs. 28.7%, p<0.001), diabetes (35% vs. 21.7%, p<0.01), and obesity (16.8% vs. 7.7%, p<0.05). Logistic regression revealed significant associations between NCDs and low physical activity (OR=8.8), tobacco use (OR=8.6), migration status (OR=3.2), and overweight/obesity (OR=6.6–7.5) compared with non-migrants. Conclusion:Migrants are at higher risk for NCDs due to lifestyle changes post-migration. These changes include low physical activity, migration status and overweight/obesity, that have significant associations with NCDs. Urgent public health interventions focusing on behaviour modification, early screening, and primary prevention are needed in migrant communities.